The New Face of Cyberbullying in Indonesia: How Can We Provide Justice to the Victims? - Prasasti Dyah Nugraheni (Universitas Negeri Semarang, 2021)
In fact, several cases of cyber oppression have increased recently as a result of internet penetration in Indonesia. Ordinarily, cyberbullying happens to celebrities and ordinary people. Ordinarily, some cases occur with suicide. As a result, based on this phenomenon, it is important to prevent forms of cyberbullying on social media, both for victims and perpetrators. Consequently, using case studies and observations, this research examines several social media services, such as Facebook, Path, Twitter, and Instagram. Accordingly, to Willory forms of cyber cyberbullying in Indonesia are harassment, defamation, identity plagiarism, fraud, and cyberstalking. Crimes in cyberspace in Indonesia, nevertheless, have three other objects besides individuals, namely cyber oppression to certain regions, religions, and institutions.